Serotonergic Mechanisms of Oocyte Germinal Vesicle Breakdown in the Mud Crab, Scylla paramamosain - Yang, Yanan; Lin, Dongdong; Bao, Chenchang; Huang, Huiyang; Ye, Haihui (Frontiers in Physiology, 2019)
The mechanism of serotonin (5-HT)-induced oocyte germinal vesicle breakdown (GVBD) in the mud crab, Scylla paramamosain, was investigated in this study. Histological staining showed that there were two meiotic arrests in oocyte, appearing at prophase I and metaphase I. This result indicated that meiosis I arrest at prophase I in S. paramamosain was similar to that of vertebrates, but meiosis II arrest at metaphase I was different from that of vertebrates. Resumption of oocytes arrest at meiosis prophase I could be induced by 5-HT rapidly within 5 min in S. paramamosain. We obtained the sequence of 5-HTR1A from the NCBI database, and found that 5-HTR1A was expressed in oocytes and follicle cells. In addition, we found that an agonist 8-OH-DPAT which binds 5-HTR1A induced GVBD and an antagonist WAY100635 which inhibited 5-HT induced GVBD in S. paramamosain. This result showed that 5-HTR1A mediated the regulation of oocyte GVBD by 5-HT. To explore the functional mechanism of 5-HT in inducing oocyte GVBD, forskolin, a cAMP agonist was used. Results showed that, forskolin significantly blocked 5-HT-induced GVBD, and there was a negative correlation between GVBD rate and cAMP level. Our data indicate that there are two meiotic arrests in S. paramamosain, and the resumption of prophase I arrest can be induced by 5-HT, which binds to 5-HTR1A, and this process is mediated by cAMP, which acts as negative regulator via cAMP signaling pathway.